Individual Performance and Employment Behavior after Maternity Leave: Evidence based on Company Data - Bernd Fitzenberger; Susanne Steffes; Anthony Strittmatter (Verein für Socialpolitik, 2010)
We analyze maternity leave durations, transition probabilities within a competing risks model and exit probabilities after maternity leave. Our sample exists of 1200 first-time mothers working in a large German company. With personnel data we observe employment histories with specific information about for instance working time and wage developments. We estimate cumulative incidence functions in order to analyze the probabilities to move into different exit states. Results show that women get their first baby when they reach the peak of their career. Less than 50 percent of all first-time mothers return to the employer within the first four years after birth. The probability to return is higher for better performing mothers who have a higher attachment to the company. These women also exhibit lower exit probabilities afterwards. These findings show that human resource strategies to reintegrate young mothers after birth are not optimal and further analyzes have to be done.
Keywords: J13; J22; M50; 330; female employment behaviour; maternity leave durations; personnel data